Optimal investment of DC pension plan with two VaR constraints. Issue 6 (19th March 2022) - Zhu, Shunqing; Dong, Yinghui; Wu, Sang
Abstract: In this paper, we investigate an optimal investment problem under two value-at-risk (VaR) constraints faced by a defined contribution (DC) pension fund manager. We apply a concavification technique and a Lagrange dual method to solve the problem and derive the closed-form representations of the optimal wealth and portfolio processes in terms of the state price density. Theoretical and numerical results show that the two VaR constraints can significantly impact the distribution of the optimal terminal wealth.